Low rate of asymptomatic carriage and salivary immunoglobulin A response to Group A Streptococci in the healthy adult population in Finland - Lönnqvist Emilia; Gröndahl-Yli-Hannuksela Kirsi; Loimaranta Vuokko; Vuopio Jaana (SPRINGER, 2025)
Streptococcus pyogenes, also called group A streptococcus (GAS), is a human pathogen causing a wide range of infections ranging from mild tonsillitis to severe, life threatening conditions such as bacteraemia, necrotizing fasciitis, and streptococcal toxic shock syndrome. GAS may also colonise the oropharynx without causing any signs of disease which is known as asymptomatic carriage. This study aims to investigate IgA responses against GAS and oral streptococci from saliva samples collected from healthy Finnish adults. In addition, asymptomatic throat GAS carriage was studied. The study participants consisted of healthy adult volunteers who provided one saliva sample, a throat swab, and a background questionnaire. Total salivary IgA, and GAS specific IgA were analysed from the saliva samples using enzyme-linked immunosorbent assays (ELISA) and the results were compared to oral streptococci specific IgA levels. Asymptomatic GAS throat carriers were identified by bacterial culture, and the isolates were emm typed. Samples from a total of 182 individuals were analysed. The median salivary IgA concentration was 62.9 mu g/ml (range 17.3-649.9 mu g/ml), and median GAS and oral streptococcal specific IgA concentrations 2.7 and 3.3 arbitrary units (AU, range 1.4-7.4 AU and 1.6-12.0 AU), respectively. Three individuals with asymptomatic GAS throat carriage were identified.